Deterministic Realization of Quasicrystal Surface Relief Gratings on Thin Azopolymer Films. Issue 11 (24th April 2020) - Salvatore, Marcella; Borbone, Fabio; Oscurato, Stefano Luigi
Abstract: Spatially structured UV–visible light fields generate topographic modulations on the surface of films of azobenzene‐containing polymers. The geometry of the surface reliefs depends on the spatiotemporal distribution of light over the sample. If multistep sequential irradiations are used, even illumination configurations as simple as the interference of two linearly polarized beams produce complex surface textures. This is the case of the quasicrystal geometries, obtainable as the superposition of multiple sinusoidal surface relief gratings oriented in different directions over the surface. The quantitative relief design would require a comprehensive theoretical description of the light‐induced relief formation mechanism, which is still elusive for azopolymers. Here, despite limiting the description at a phenomenological level, the deterministic design of the quasicrystal surface reliefs obtained in sequential light exposures of an azopolymer film is demonstrated. The model provides an excellent agreement between simulated and experimental relief textures, predicting also the dependence of relief structural features on illumination parameters as the number of exposure steps and the beam interference angle. The deterministic texture design allows the controlled tailoring of surface functionalities related to the relief geometry like light diffraction properties of the samples, which are here exploited to manipulate, split, and trap diffracted light. Abstract : The ability to accurately realize versatile complex surface textures is of great relevance for tailoring functionalities related to the surface geometry. In this work, the design of light‐induced quasicrystal surface reliefs on azopolymer films whose geometry and light diffraction behavior are deterministically predicted by means of a phenomenological model for the mass migration is demonstrated.